Guide for Educators Lost in the Global Village - Cruz Fuentes, Immanuel (2021)
This essay is a metaphorical guide to help the educators of today to circulate through the global city in which we live in the 21st century. As part of the tour, the reader will be directed safely to those “zones” of the great global village in which education has been developed, allowing them to know places of interest of the current pedagogical theory, spots that they must visit to understand how virtual/digital technologies have become important; at the same time, they have displaced the physical/face-to-face experience and meeting points to share our didactic experiences. Finally, we will take a walk, in which the author will explain the shortcuts that he has discovered to mobilize in the midst of the global city, how to learn to enjoy the view of education that is presented to us, and what could be expected from the horizon that we can see for the future of teaching and learning in the 21st century.